Levantamento sociodemográfico e análise comparativa da qualidade de vida de idosos de diferentes bairros do município de Altamira, Pará, Brasil - TAPAJÓS, Anakarinny Dias Melo (2022)
The age structure of Brazil has been experiencing a rapid transition, with a significant increase in the number of elderly people. Aging with quality has proved to be a great challenge, for this reason it is important to understand aging in all its aspects and dimensions. The objective of this study was to compare the sociodemographic and quality of life profile of the elderly in the districts of Centro, Brasília and Jatobá, located in the municipality of Altamira, Pará, Brazil. Regarding the method used, it was a semi-quantitative, descriptive-analytical research, which was carried out in three Health Units as well as their coverage area. 96 elderly people from Brasília, 80 from Centro and 84 from Jatobá participated in the study. For data collection, a sociodemographic data form and the World Health Organization Quality of Life – OLD instrument were used. For analytical statistics, the Kruskal-Wallis non-parametric test and Dunn's Post-Hoc test available in the GraphPad Prism 9 Software were used, and Excel 2019 was used for tabulation and descriptive statistics. The general sociodemographic results were a prevalence of elderly of the sex female, most aged between 60-69 years, who declared themselves to be brown, mostly married, with reduced education, retired and with a family arrangement composed of the elderly with one or two more people. Regarding the quality of life, there was a significant difference between the elderly from different neighborhoods, with a value of p < 0.05, with better results from the Brasília neighborhood over the others in the sensory functioning and autonomy domains, while the Center excelled in terms of quality of life. domain of past, present and future activities and Jatobá was highlighted in the intimacy domain. In the domain of death and dying, the Brasília and Centro neighborhoods had the same score, which was higher than the one presented by the Jatobá neighborhood. And with regard to the domain of social participation, there were no significant differences. In terms of general quality of life, the elderly in the Brasília neighborhood presented the best result, followed by the elderly in the Centro neighborhood, who stood out over those in the Jatobá neighborhood, however, all of them presented a regular rating on the Likert scale. It is concluded, therefore, that from the evaluation of the six domains of quality of life, it became evident that there are significant differences between the elderly in the evaluated neighborhoods, and these possibly establish a relationship with the sociodemographic profile, so it is necessary to reorganize policies of inclusion and care with equity for this part of the population.